Glass-ceramics with reduced lithium content
Patent Information
- Application Number
- CN202611473319.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-05-07
- Filing Date
- 2018-12-20
- Publication Date
- 2026-10-30
AI Technical Summary
该SiO2份额提高了熔化温度,结果导致熔化的较高能量成本
Smart Images

Figure CN123003151A_ABST
Abstract
Description
[0001] This invention is a divisional application of Chinese Patent Application No. 201811560946.8 entitled "Glass-ceramic with reduced lithium content" filed on December 20, 2018.
[0002] Invention Field This invention relates to a transparent colored glass ceramic, which is suitable for use as a cooktop. Background of the Invention Glass-ceramic cooktops and the glass ceramics used for this purpose have been known for many years. Typically, lithium aluminum silicate (LAS) glass ceramics are used, particularly for transparent materials containing a high-quartz solid solution as the main crystalline phase, or particularly for translucent or opaque materials containing a hydrothermal quartz solid solution as the main crystalline phase. A fundamental characteristic of these materials used as cooktops is the very small thermal expansion from room temperature to 700°C and above, achieved through a combination of a negatively expanding crystalline phase and a positively expanding amorphous residual glass phase. To achieve this, the crystalline phase content must be sufficiently high, typically greater than 50%, preferably even greater than 60%. In the glass ceramics used to date, a lithium content of typically 4 to 5% by weight is used for this purpose.
[0004] When transparent glass-ceramics with a high quartz solid solution as the main crystalline phase are used for cooktops, they are either colored by adding color oxides or provided with an undercoat to visually conceal the technical devices located beneath the cooktop. Different color oxides can be used to color glass-ceramics, some of which, such as CoO, NiO, Nd2O3, or CuO, can significantly increase the price of glass-ceramics due to their high raw material costs.
[0005] Although arsenic oxide and / or antimony oxide, known refining agents in the glass industry, have been primarily used in the past, other less toxic alternatives such as tin oxide (SnO2) are preferred as clarifiers for environmental and occupational safety reasons.
[0006] Transparent glass-ceramics that can be optionally colored with V₂O₅ are described in DE1796298A1. Here, the colored oxides NiO and CoO are preferred, and the coloring using only V₂O₅ combined with ZnS is disclosed, because a red glass-ceramic is to be produced.
[0007] Coloring with V2O5, Cr2O3 and CoO or CuO is described in publications US4526872A, JP6086311B4 and EP2435378B1.
[0008] DE3345316A1 describes colored glass-ceramics with low lithium content for use in the production of colored stovetops. Here, at least 0.1% by weight is colored with vanadium oxide, as disclosed in German Patent DE19939787C2 and European Patent EP1313675B2, in which glass-ceramics colored with V2O5 and purified with SnO2 are used for stovetops.
[0009] Japanese patent applications JP11100229A and JP11100230A describe glass-ceramics colored with vanadium oxide, which are clarified with SnO2 and optionally with Cl- additives.
[0010] EP1398303B1 also discloses ceramizable glasses for the production of glass-ceramics, which may optionally be colored with V2O5. The compositions described therein are clarified with As2O3 or Sb2O3.
[0011] It is also disclosed that adding 0.05 to 1% by weight of fluorine (US20070004578A1) and 0.01 to 1% by weight of bromine (US20080026927A1) can help with clarification with SnO2. However, the addition of halides is disadvantageous because they evaporate strongly at melting temperatures and may form toxic compounds such as HF.
[0012] Clarification using a combination of SnO2 and CeO2 and / or MnO2 is described in application US2007129231A. However, this requires 0.7% to 1.5% CeO2 or MnO2. However, the economic viability is questionable because the raw material prices of these two components are significantly higher than those of SnO2.
[0013] DE102008040097B4 illustrates the coloring of glass ceramics by means of a small amount of V2O5 (in the range of 0.003 to 0.7% by weight).
[0014] In the prior art, for example in DE102008050263B4 and DE102009013127B4, transparent glass-ceramics with specially set transmittance at specific wavelengths are also described. For this purpose, it is preferable to use combinations of different coloring oxides with V2O5, such as CoO, Nd2O3, and NiO.
[0015] US8765619 discloses glass-ceramics using V2O5 as a coloring oxide and Fe2O3, NiO and MnO as co-coloring agents.
[0016] A combination of vanadium oxide and CoO was also proposed for coloring glass-ceramic cooktops (WO1013700A1). However, the expected batch price is higher here compared to V2O5 coloring without CoO.
[0017] US document US2013070451A describes a display device with glass-ceramic components, which may contain 100 to 2000 ppm of V₂O₅ and 0.1 to 0.5 wt% of SnO₂. A reduction in Li₂O is described in this example; however, this is detrimental to the coefficient of thermal expansion for cooktop applications at low BaO content (0.8 wt%) and MgO content (1.3 wt%).
[0018] WO11089220A1 discloses high-quartz glass-ceramics that are particularly optimized for clarification with SnO2. Here, CoO is preferably used as a co-coloring agent in addition to V2O5.
[0019] US application US2013098903A exemplifies a glass-ceramic for cooktops containing V₂O₅ as a colorant, SnO₂ as a clarifying agent, and 3.5% by weight of lithium. The SiO₂ content of this glass-ceramic is 69.9% by weight. This SiO₂ content increases the melting temperature, resulting in higher energy costs for melting.
[0020] PCT application WO12010278A1 also discloses a colored cooktop having a lithium content of 1.5 to 4.2% by weight and SnO2 as a clarifying agent. Here, a combination of at least two coloring oxides is used.
[0021] US Patent No. 8722554B discloses a glass-ceramic dyed using V₂O₅, specifically optimized for clarification with SnO₂. For this purpose, for example, compositions with a Li₂O content greater than 3.7% by weight are mentioned.
[0022] Purpose of the invention The purpose of this invention is to provide a transparent colored glass ceramic that has good raw glass melting performance and is inexpensive, without limiting its performance.
[0023] In particular, glass ceramics should meet all the requirements for use as cooktops, such as low thermal expansion, sufficient chemical resistance, thermal shock resistance and long-term temperature resistance, and suitable optical transmission. Summary of the Invention
[0024] The object of the invention is achieved by the subject matter of claim 1. Preferred examples and improvements can be found in the dependent claims.
[0025] The transparent colored glass-ceramics according to the present invention, particularly LAS glass-ceramics, contain high quartz mixed crystals (HQMK, high quartz solid solution) as the main crystalline phase, and their thermal expansion in the range of 20°C to 700°C is -1 to +1 ppm / K, preferably -0.6 to +0.6 ppm / K, more preferably -0.5 to +0.5 ppm / K.
[0026] This ensures sufficient resistance to thermal shock.
[0027] Because the glass-ceramic according to the present invention contains high-quartz solid solution as the main crystalline phase, it means that the proportion of high-quartz solid solution as the crystalline phase is greater than 50% of the total crystalline phase present.
[0028] Furthermore, the glass-ceramic according to the present invention contains 3.0 to 3.6 weight percent of lithium oxide (Li2O) as a component. This can reduce the production cost of the glass-ceramic.
[0029] Furthermore, the glass-ceramic according to the invention is colored with 0.003 to 0.05% by weight of vanadium oxide (V2O5) as a coloring oxide, preferably 0.026 to 0.033% by weight.
[0030] As a substitute for component V2O5, 0.003 to 0.25% by weight of molybdenum oxide (MoO3) is used as the coloring oxide.
[0031] Even with molybdenum oxide (MoO3), economical production is achievable. However, vanadium oxide (V2O5) is a stronger colorant than molybdenum oxide (MoO3). Therefore, less V2O5 is needed for the same coloring, making the use of V2O5 more economical. However, molybdenum oxide has a shallower transmission distribution in the visible range, which is advantageous for white light-emitting elements.
[0032] Since other coloring oxides, such as CoO, NiO, Nd2O3 or CuO, would significantly increase the price of glass ceramics due to their high raw material costs, in the glass ceramics according to the invention, coloring is preferably produced only by means of vanadium oxide (V2O5) or molybdenum oxide (MoO3), wherein the small amount is sufficient for adequate coloring.
[0033] Therefore, for cost reasons, using other coloring oxides is generally not worthwhile. Using coloring oxides with very strong coloring effects, such as CoO, NiO, Cr2O3, or CuO, can also introduce unwanted impurities or cross-contamination, as even small amounts can significantly affect the resulting color. The amount of these coloring oxides should be limited to the amount introduced by impurities. This is equivalent to 0 to less than 0.01% by weight for each of CoO, NiO, Cr2O3, CuO, or Nd2O3, and 0 to less than 0.03% by weight for MnO2.
[0034] Since sufficient color effects can be obtained even using V2O5 or V2O5 as the sole coloring oxide, the use of the aforementioned coloring oxides can be omitted.
[0035] The lower Li₂O content compared to conventional glass ceramics allows for reduced raw material costs, as the cost of lithium raw materials has increased significantly in recent years due to increased demand (e.g., for lithium-ion batteries). This makes the production of economically attractive glass ceramics, particularly for cooktops, advantageously reducing the amount of lithium required for this purpose.
[0036] However, a decrease in the Li2O content in lithium aluminum silicate (LAS) glass ceramics can lead to a decrease in the crystalline phase content, which in turn leads to an increase in thermal expansion.
[0037] This can be compensated for by adding magnesium oxide (MgO), preferably in the range of 0 to at most less than 1% by weight. Particularly preferred, the glass ceramic contains 0.3 to less than 1% by weight of MgO, and most preferably at most 0.77% by weight of MgO.
[0038] To further offset the increase in thermal expansion, in a preferred embodiment, the amount of zinc oxide (ZnO) added can be 1.2-2.5% by weight. Higher ZnO additions exceeding 2.5% by weight result in the formation of zinc spinel (Gahnit) as an undesirable secondary crystalline phase.
[0039] However, the reduction of alkaline earth metal oxides may simultaneously lead to an undesirable increase in melting temperature. This effect can be mitigated by advantageously adding 1.2 to 2.8 wt% BaO.
[0040] Therefore, the selection of the above-mentioned optimal weight percentage range of MgO and the specific addition of ZnO and BaO can be used to adjust viscosity and reduce melting temperature.
[0041] The combination of coloring with only V2O5 or MoO3 and low lithium content, preferably with MgO content reduced to less than 1% by weight, and the potential selection of a BaO content in the optimal weight percentage range of 1.2 to 2.8% by weight and an addition of zinc oxide (ZnO) in the range of 1.2-2.5% by weight, results in optimized melting temperature and thermal expansion, and leads to glass ceramics with particularly good performance and are particularly economically advantageous.
[0042] In a particularly advantageous embodiment of the glass-ceramic, the ratio of (BaO+ZnO) / MgO (given as a weight percentage) is correspondingly in the range of 2.2 to 35 wt%, preferably in the range of 4.5 to 15 wt%.
[0043] Preferably, the glass ceramic is clarified with 0.1 to 0.6% by weight of tin oxide (SnO2). A SnO2 content greater than 0.6% by weight will adversely affect solubility and increase the tendency for devitrification. Using tin oxide also eliminates the need for health-hazardous clarifying agents.
[0044] The particularly preferred glass ceramic contains the following components in weight percentage: SiO2 62 to 68 Al2O3 18.5 to 23 Li2O 3.0 to 3.6, preferably 3.2 to 3.6. V₂O₅ 0.003 to 0.05 or MoO₃ 0.003 to 0.25 SnO2 0.1 to 0.6 BaO 1.2 to 2.8 MgO 0 to less than 1, preferably 0.3 to less than 1 ZnO 1.2 to 2.5 TiO2 2.6 to 4.5 ZrO2 0.9 to 1.7 B2O3 0 to 2 P2O5 0 to 4 Na₂O + K₂O 0 to less than 1.5, preferably less than 1 CaO 0 to less than 1 SrO 0 to less than 1 Fe2O3 0 to 0.2, preferably up to 0.15.
[0045] In preferred glass-ceramics, the listed components comprise at least 96% by weight of the total composition, typically at least 98% by weight. In addition to the components mentioned, impurities commonly found in raw materials used in large-scale engineering may also be included in the glass-ceramics.
[0046] SiO2 and Al2O3 components, along with Li2O, form the main components of the high-quartz solid solution phase in glass-ceramics. They also essentially determine the glass-forming properties and the viscosity of the raw glass used to produce glass-ceramics. The Al2O3 content is preferably in the range of 18.5 to 23% by weight, with lower amounts leading to an undesirable increase in viscosity. Higher Al2O3 content enhances devitrification tendency and promotes undesirable mullite formation.
[0047] The optimal range for SiO2 content is preferably between 62 and 68% by weight. Glass ceramics with lower SiO2 content may exhibit disadvantages in performance aspects important for cooktops, such as chemical resistance and heat resistance. On the other hand, with raw glass having higher SiO2 content, the melting temperature increases, resulting in higher energy costs during the glass ceramic production process.
[0048] TiO2, ZrO2, and preferably SnO2 for clarification are used as nucleating agents. To ensure effective nucleation even with short ceramization times, the glass-ceramic advantageously contains at least 2.6 wt% TiO2 and at least 0.9 wt% ZrO2. The upper limit of the nucleating agent content stems from the requirement for anti-vitrification stability and to avoid unwanted heterogeneous phases. High ZrO2 content also leads to a significant increase in the required melting temperature. The total amount of nucleating agent should not exceed 6 wt%.
[0049] B₂O₃ and P₂O₅ can improve the solubility of glass, but larger amounts negatively affect its thermal expansion and heat resistance. In particular, phosphorus can also reduce the ceramization rate, thus requiring a longer ceramization time.
[0050] Alkali metal oxides Na₂O and K₂O are preferably used in small amounts, that is, a total of a maximum of 1.5% by weight, preferably a maximum of 1% by weight, in order to reduce viscosity. Similarly, the use of CaO and / or SrO up to less than 1% by weight can be helpful. However, larger amounts of these oxides lead to the formation of heterogeneous phases, which increases the unacceptable thermal expansion.
[0051] Since sufficient color effects can be obtained using V2O5 or alternatively MoO3, as mentioned above, the use of coloring oxides CoO, NiO, Cr2O3, CuO, Nd2O3, or MnO2 should be omitted.
[0052] An exception is Fe2O3, which may be present in amounts of 0 to 2% by weight, preferably up to 1.5% by weight, depending on the type of raw material used. Small amounts of Fe2O3 can aid in the clarification process and allow the use of inexpensive raw materials. Therefore, combining the above-mentioned components in the above-mentioned limits helps improve solubility and quality, as well as reduce costs.
[0053] For environmental protection and occupational safety reasons, the use of toxic or problematic raw materials should be avoided as much as possible. Therefore, the glass ceramics are preferably free of environmentally harmful substances, namely arsenic (As), antimony (Sb), cadmium (Cd), lead (Pb), cesium (Cs), rubidium (Rb) halides, and sulfur (S), except for unavoidable impurities, preferably ranging from 0 to less than 0.5% by weight, more preferably less than 0.1% by weight, and most preferably less than 0.05% by weight. The weight percentage refers to oxide-based glass compositions.
[0054] Generally, naturally occurring raw materials or chemically or synthetically prepared raw materials can be used. Naturally occurring raw materials are usually cheaper than their equivalent chemically prepared or synthetic counterparts. However, the utility of natural raw materials is often limited by their high impurity content. Examples of naturally occurring raw materials are quartz sand, spodumene, and petalite. Chemically prepared or synthetic raw materials typically contain very few impurities. Commonly used examples of prepared or synthetic raw materials are lithium carbonate or titanium dioxide powder.
[0055] Depending on the composition, specific limits for these impurities should not be exceeded. In particular, in addition to the components already mentioned above, the proportion of Cr2O3 in the glass composition should be limited to less than 0.02% by weight, preferably less than 0.01% by weight, and especially less than 0.005% by weight.
[0056] In a preferred embodiment, the statement that the glass-ceramic contains high-quartz mixed crystals (HQMK, high-quartz solid solution) as the main crystalline phase means that the proportion of high-quartz solid solution as the crystalline phase is greater than 80%, preferably greater than 90%, of the total crystalline phases present. When thermal expansion requirements need to be met, a small amount, i.e., up to 20%, or preferably up to 10%, particularly preferably up to 5%, of hydrothermal quartz solid solution, especially crystalline phases containing nucleating phases of Ti, Zr, or Sn, may be included.
[0057] However, it is preferable to avoid the formation of other, especially highly expanding, crystalline phases, such as sodium aluminum silicate or potassium aluminum silicate, or sodium silicate or potassium silicate.
[0058] For the preferred glass-ceramic, with a thickness of 4 mm, the light transmittance (τ) measured according to DIN EN 410 is... vis The concentration is 0.5% to 70%, preferably 0.5% to 40%, particularly preferably 0.5% to 30%, and very particularly preferably 0.5% to 20%. Depending on the application, a range of 0.5% to 5% or even 0.9% to 2% may be preferred.
[0059] This ensures that the technical components beneath the cooktop will not be perceived as distracting by the observer.
[0060] To achieve good visibility of the display element, such as a color LED, below the cooktop, the transmittance value is greater than 0.1%, preferably greater than 0.15%, across the entire wavelength range above 450 nm.
[0061] A transmittance range of 0.5 to 10% is particularly important for LED-based displays and light sources, such as 7-segment displays.
[0062] A transmittance range of 10% to 70%, preferably 30% to 40%, is particularly advantageous for the use of TFT displays.
[0063] Therefore, these glass-ceramics are particularly well-suited for use in light-emitting display elements and other light-emitting components. Examples include LEDs, 7-segment displays, TFT displays, especially LCD and OLED-TFT displays, or image or video projectors that project images through the glass-ceramics. These elements can be monochromatic or multicolor. In particular, red, green, blue, or white elements are considered as monochromatic elements. Multicolor elements include those that can display at least two primary colors simultaneously and those that can alternately display at least two colors. Such light-emitting elements can also be used in conjunction with scattering or diffusing elements attached to the glass-ceramics. For example, scattering and diffusing elements are used for spatial homogenization of luminous intensity or for widening the viewing angle that can be perceived by the light-emitting element.
[0064] The V₂O₅-based coloring implementation is particularly suitable for monochrome red displays and lighting elements, especially red LEDs, red 7-segment displays, and red TFT displays. The MoO₃-based coloring implementation is also particularly suitable for white and multicolor displays and lighting elements, especially white or RGB-LEDs, white or RGB-7-segment displays, and color TFT displays or color projectors.
[0065] In infrared light, the transmittance is high enough to ensure good cooking properties. Preferably, the transmittance is 45% to 85% at 1600 nm.
[0066] In a preferred embodiment, the glass melt of the glass-ceramic blank reaches a viscosity of 200 dPa·s at a temperature below 1750°C, preferably below 1700°C.
[0067] The thermal expansion in the range of 20°C to 700°C is preferably in the range of 0 to 0.41 ppm / K, more preferably in the range of 0 to 0.35 ppm / K, and particularly preferably in the range of 0 to 0.3 ppm / K.
[0068] Glass-ceramics are preferably used as cooktops, fireplace windows, grill or baking surfaces, covers for fuel elements in gas grills, oven doors, especially for pyrolysis cookware in kitchens or laboratories, work surfaces or tabletops, covers for lighting fixtures, fireproof glass and as safety glass, optionally in laminated composites, as back panels or furnace linings in heat treatment, or as back covers for mobile electronic devices.
[0069] Glass-ceramics are particularly suitable for cooktops with radiant heating elements, halogen heating elements, induction heating devices, or gas heating elements. The cooktop may be wholly or partially decorated on the top and / or bottom surfaces. Similarly, touch sensors for operating the cooktop may be provided on the bottom surface. These can be, for example, printed, glued, or pressed capacitive sensors.
[0070] Furthermore, the cooktop can also be three-dimensionally formed; that is, the plate can be angled or curved, or include areas shaped like, for example, a wok. For instance, recesses for operating the gas burner are also feasible.
[0071] The preparation of glass ceramics is preferably carried out in the following steps.
[0072] First, the raw materials, and preferably broken glass, are melted. Preferably, the melting of the raw glass is carried out at a temperature of 1500°C to 1700°C.
[0073] The clarification of raw glass melt is preferably carried out using SnO2.
[0074] Following mass production is the thermoforming process, preferably roll forming or float forming, to produce glass-ceramic sheets. Forming is carried out within a processing temperature range, preferably with a viscosity of 10. 4 dPas. This temperature should preferably be below 1350°C, and particularly preferably below 1330°C.
[0075] To avoid crystallization during the molding process, the processing temperature (V) A The difference between the upper limit of the devitrification temperature (V) and the upper limit of the devitrification temperature. A -OEG) should preferably be between 20 and 100°C.
[0076] The ceramization of the glass-ceramic plate is preferably carried out in a two-stage process, in which initial nucleation occurs at 680°C to 800°C. Subsequently, the temperature is raised to 850°C to 950°C to grow a high-quartz solid solution (HMQK) on the nuclei. For this purpose, the temperature is chosen so high that ceramization is achieved as quickly as possible, but the transformation of the high-quartz solid solution (HQMK) to a hydrothermal quartz solid solution (KMK) does not occur. During the transformation from high-quartz to hydrothermal quartz, thermal expansion increases, and scattering increases due to the increase in crystallite size. Both of these effects are to be avoided in this invention.
[0077] In the following text, reference will be made to the embodiments and Tables 1 through 5 (each with a and b), and further reference will be made to... Figure 1 The invention will be explained in more detail below.
[0078] Tables 1 to 5 show the weight percentages and properties of the compositions after analysis, particularly the preferred glass ceramics and related raw glass, such as Examples 1 to 27 (each having a and b) in Tables 1 to 4 and the non-inventive comparative examples V1 to V5 in Tables 5a and 5b.
[0079] Table 1a: Examples 1 to 8 Table 1b: Examples 1 to 8 Table 2a: Examples 9 to 16 Table 2b: Examples 9 to 16 Table 3a: Examples 17 to 21 Table 3b: Examples 17 to 21 Table 4a: Examples 22 to 27 Table 4b: Examples 21 to 27 Table 5a: Comparative Examples V1 to V5 Table 5b: Comparative Examples V1 to V5 The starting glass compositions shown in Tables 1 to 5 are analyzed weight percentage compositions, melted in crucibles made of sintered silica glass at 1600 to 1650 °C for 4 hours. They were then poured into silica crucibles at 1550 to 1580 °C and homogenized by stirring for 30 minutes. Clarification with tin oxide was then carried out at 1620 to 1640 °C for 2 hours.
[0080] The glass is poured into the casting, which is below the transformation temperature (T). g Slowly cool to room temperature in a cooling furnace at a temperature of approximately 20°C.
[0081] Some castings are used to determine glassy properties. The viscosity was measured at 10. 4 Processing temperature (V) at dPa•s aThe temperature corresponding to a viscosity of 200 dPa•s is also considered. In some cases, the upper limit of devitrification temperature (OEG) is determined after 5 hours of Pt contact.
[0082] The abbreviation 'nb' used in the table indicates that this data has not yet been determined.
[0083] In addition, samples for measuring glass-ceramic properties are manufactured from castings and then ceramicized.
[0084] The following temperature-time profiles are used in the ceramization process: It can rapidly heat from room temperature to 740°C in 26 minutes. The temperature rose from 740°C to 825°C in 18 minutes (heating rate of 4.7°C / minute). The temperature rises from 825℃ to 930℃ within 4 minutes (heating rate 26℃ / minute), and is maintained at the maximum temperature of 930℃ for 4 minutes. d) Cool to 800°C within 16 minutes, then rapidly cool to room temperature.
[0085] Rietveld analysis was used to perform XRD measurements on the ceramicized samples to determine the crystal phase and crystallite size.
[0086] Since the determination of amorphous phases involves a great deal of uncertainty, the crystalline phase compositions given in the table are based on the total crystalline phase content of the glass ceramic.
[0087] Transmittance was measured on samples with thicknesses ranging from 3 mm to 4 mm and then converted to a 4 mm thickness for better comparability. Transmittance (τ) was measured according to DIN EN 410. vis (Listed in the table.)
[0088] Thermal expansion (α) was measured in the range of 20°C to 700°C.
[0089] The density of some samples in the ceramized state was also measured.
[0090] Examples 1 to 27 shown in Tables 1a and 1b, 2a and 2b, 3a and 3b, and 4a and 4b are examples of glass ceramics according to the invention, while Examples V1 to V5 are comparative examples not of the invention, as shown in Tables 5a and 5b.
[0091] The glass-ceramics according to the invention, derived from Examples 1 to 27, have a processing temperature (V) of 1281°C to 1341°C. A The upper limit of devitrification temperature (OEG) is between 1226°C and 1325°C.
[0092] By appropriately selecting the composition, it is possible to obtain a particularly devitrifying and stable preform glass melt, that is, a melt with a particularly large difference (Vo) from the processing temperature to the upper limit of the devitrification temperature. A -OEG). This may be necessary depending on the requirements of the chosen thermoforming process.
[0093] The temperature at which the viscosity of the raw glass melt is 200 dPa•s is between 1591°C and 1699°C in the example of this invention.
[0094] In the example according to the invention, after the above-described ceramization, all the melt of the raw glass has high-quartz (HQMK) as the main crystalline phase, typically exceeding 90% of the total crystalline phase fraction. Other crystalline phases are hydrothermal quartz solid solution (KMK) and nucleating agent phases ZrTiO4 and rutile (TiO2). Simultaneously, the crystallite size is very small, ranging from 33 nm to 73 nm. No interference scattering occurs when the display element is used beneath the glass-ceramic.
[0095] transmittance (τ) vis This translates to a thickness of 4 mm, which in the example is 0.6 to 38.5%.
[0096] Figure 1 The transmission spectrum of the sample according to the invention from Example 12 is shown.
[0097] The sample in Example 12 shows a transmittance of 74% for infrared light (1600 nm). The glass-ceramic has a transmittance of 1.0% at 470 nm and is greater than this value at all wavelengths. Therefore, this demonstrates the good display capability of the color LED.
[0098] In the glass-ceramic according to Example 12, the light transmittance (τ) vis The figure was 3.7%.
[0099] Example 17 shows a high visible light transmittance of almost 20% (Table 3b). This could be advantageous if an undercoating is to be used or if the display element is mounted under the glass-ceramic.
[0100] Example 19 uses cheaper raw materials for melting. As a result, 0.0041 wt% Cr₂O₃ impurities and 0.00032 wt% Rh impurities are introduced through crucible contact. As can be seen from the properties listed in Tables 3a and 3b, despite this, the desired characteristics are achieved for the glass-ceramic cooktop.
[0101] Example 20 illustrates coloring with MoO3. This composition contains 0.16% MoO3 (Table 3a) and has a transmittance of 5% (τ) in the ceramized state. vis (Table 3b).
[0102] Tables 4a and 4b list other examples of coloring with MoO3. The transmittance (τ) of the examples colored with MoO3 is also provided. vis The transmittance also ranges from 0.6% to 38.5%. Higher and lower transmittances can be achieved by adjusting the composition accordingly.
[0103] According to the examples, the thermal expansion (α) of the glass ceramics is 0.07 to 0.59 ppm / K in the range of 20 to 700°C (Tables 1b, 2b and 3b), which corresponds to the requirements of a temperature-stable cooktop.
[0104] The comparative examples V1 to V5 in Table 5a (not comparative examples of the present invention) illustrate the selection of composition ranges.
[0105] Comparative examples V1 and V2 contain excessively high levels of MgO (Table 5a). Both exhibit hydrothermal quartz solid solution (KMK) as the dominant crystalline phase and correspondingly high thermal expansion (α), as shown in Table 5b. This is also due to the excessively high SiO2 content in comparative example V1 and the excessively low Li2O content in V2 (Table 5a).
[0106] Comparative example V3 has a lithium content of 3.8% (Table 5a). Although glass-ceramics have good properties, they have higher raw material costs due to their high lithium content, and therefore do not offer any advantages over known prior art.
[0107] Compared with the glass ceramics according to the invention, Comparative Example V4 also has an excessively high MgO content of 1.11 wt% and an excessively low Li2O content, as shown in Table 5a, which increases the thermal expansion between 20°C and 700°C to 0.6 ppm / K (Table 5a).
[0108] Comparative Example V5 illustrates the negative impact of excessively high MgO content (Table 5a) on thermal expansion, where thermal expansion increases to 0.91 ppm / K (Table 5b).
Claims
1. A transparent colored glass-ceramic, particularly a LAS glass-ceramic, comprising a high-quartz solid solution (HQMK) as the main crystalline phase and having a thermal expansion of -1 to +1 ppm / K in a temperature range of 20°C to 700°C, wherein the glass-ceramic contains 3.0-3.6 wt% lithium oxide (Li2O) as a component and is colored with 0.003-0.05 wt% vanadium oxide (V2O5) or 0.003-0.25 wt% molybdenum oxide (MoO3).
2. The glass-ceramic according to claim 1, comprising 0 to less than 0.01% by weight of coloring oxides CoO, NiO, Cr2O3, CuO or Nd2O3 and 0 to less than 0.3% by weight of MnO2.
3. The glass-ceramic according to claim 1 or 2, comprising the following components by weight percentage: alkaline earth metal oxides and ZnO: BaO 1.2 to 2.8 MgO 0 to less than 1 CaO 0 to less than 1 ZnO 1.2 to 2.
5.
4. The glass-ceramic according to one or more of the preceding claims, which is clarified using 0.1 to 0.6% by weight of tin oxide (SnO2).
5. The glass-ceramic according to one or more of the preceding claims, comprising the following components by weight percentage: SiO2 62 to 68 Al2O3 18.5 to 23 Li2O 3.0 to 3.6, preferably 3.2 to 3.
6. V₂O₅ 0.03 to 0.05 or MoO₃ 0.003 to 0.25 SnO2 0.1 to 0.6 BaO 1.2 to 2.8 MgO 0 to less than 1, preferably 0.3 to less than 1 ZnO 1.2 to 2.5 TiO2 2.6 to 4.5 ZrO2 0.9 to 1.7 B2O3 0 to 2 P2O5 0 to 4 Na₂O + K₂O 0 to less than 1.5, preferably less than 1 CaO 0 to less than 1 SrO 0 to less than 1 Fe2O3 0 to 0.2, preferably up to 0.
15.
6. The glass-ceramic according to one or more of the preceding claims, wherein the ratio of (BaO+ZnO) / MgO is in the range of 2.2 to 35 by weight, preferably in the range of 4.5 to 15.
7. The glass ceramic according to one or more of the preceding claims, wherein the amount of the compound containing arsenic (As), antimony (Sb), cadmium (Cd), lead (Pb), halide or sulfur (S) is 0 to less than 0.5% by weight, preferably less than 0.1% by weight, more preferably less than 0.05% by weight.
8. The glass-ceramic according to one or more of the preceding claims, comprising a high-quartz solid solution (HQMK) as the main crystalline phase, the amount of which is more than 80%, preferably more than 90%, and comprising only nucleating phase or hydrothermal quartz solid solution (KMK) as other crystalline phases, the content of which is at most 20%, preferably at most 10%, particularly preferably at most 5%, of the crystalline phase share.
9. The glass-ceramic according to one or more of the preceding claims, wherein the light transmittance (τ) is [value missing] when the thickness is 4 mm. vis The content of ) is 0.5% to 70%, preferably 0.5% to 40%, particularly preferably 0.5% to 30%, and most preferably 0.5% to 20%.
10. The glass-ceramic according to one or more of the preceding claims, wherein the raw glass melt of the glass-ceramic achieves a viscosity of 200 dPa•s at a temperature below 1750°C, preferably below 1700°C.
11. The glass-ceramic according to one or more of the preceding claims, wherein the thermal expansion in the range of 20°C to 700°C is 0 to 0.41 ppm / K, preferably 0 to 0.35 ppm / K, and particularly preferably 0 to 0.3 ppm / K.
12. Uses of the glass-ceramic according to one or more of the preceding claims, for use as cooktops, fireplace windows, grilling or baking surfaces, covers for fuel elements in gas grills, oven doors, particularly for pyrolysis cookware in kitchens or laboratories, work surfaces or tabletops, covers for lighting fixtures, fireproof glass and as safety glass, optionally in laminated composites, and as back panels or furnace linings in heat treatment, or as back covers for mobile electronic devices.
13. A method for manufacturing glass-ceramics according to one or more of claims 1 to 11, the method comprising the following steps: - Melting of raw material components, wherein the melting of the raw glass is preferably carried out at a temperature of 1500 to 1700°C. - To clarify the melt of the raw glass, SnO2 is preferred. -At the processing temperature (V) A Within the temperature range of ), preferably at 10 4 At a viscosity of dPa•s, it is more preferable to thermoform the glass-ceramic plate at a temperature below 1350°C, wherein the processing temperature (V A The difference between (V) and the upper limit of devitrification temperature A -OEG) is preferably kept between 20 and 100 °C. - Ceramization, in which the speed and temperature are chosen in such a way that the high quartz solid solution (HQMK) is prevented from transforming into hydrothermal quartz solid solution (KMK).
Citation Information
Patent Citations
Black tinted LAS glass ceramic
DE102008040097B4
Transparent, colored cooking surface with improved color display capability and method for manufacturing such a cooking surface
DE102008050263B4
Transparent, colored cooking surface and method for indicating an operating state of such a surface
DE102009013127B4
COLORED TRANSPARENT GLASS-CERAMIC WITH LOW THERMAL EXPANSION COEFFICIENT AND PROCESS FOR THEIR PRODUCTION
DE1796298B
transparent glass ceramic that can be colored dark with the addition of vanadium oxide, with high quartz mixed crystals as the predominant crystal phase, process for their production and their use
DE19939787C2
